Ajuste da viscosidade do fluido erosivo para manutenção da eficiência do processo de usinagem por hidroerosão - Moreira, Pâmela Portela (2015)
Hydroerosive grinding process is used on nozzle injectors for diesel system in order to improve its performance by rounding the internal diameter of the injection channels through which flows the diesel for injection in the engine. The efficiency of hydroerosive grinding process is related to the conditions of the erosive fluid used in the process, for which viscosity has a major role for efficiency maintenance. Coupling between particles and fluid is affected by viscosity decrease along time, thus influencing material removal rate efficiency and causing productivity losses, once cycle time increases to achieve the specified material removal rate. In the present investigation, the process efficiency was evaluated during 160 hours using viscosity correction of the erosive fluid in order to keep viscosity close to its initial work condition. The root cause for viscosity decrease was also investigated through evaluation of possible contamination of the erosive media by lower viscosity fluids existing in the process. After 160 hours of process monitoring with viscosity adjustment, it was observed 8,8 % of viscosity reduction considering the first and the last samples, besides that the material removal rate efficiency decreased only 4,2 % over 20 % decrease observed in a previous study related to hydroerosive grinding process without particle replacement and viscosity adjustment. Contamination of the erosive fluid by measurement oil used in the previous station was responsible for 37,5 % of viscosity decrease along 40 hours of production.